Two-proton radioactivity of the excited state within the Gamow-like and modified Gamow-like models - Zhu, De-Xing; Xu, Yang-Yang; Liu, Hong-Ming; Wu, Xi-Jun; He, Biao; Li, Xiao-Hua (Nuclear science and techniques, 2022)
In this study, we systematically investigated the two-proton ( 2p ) radioactivity half-lives from the excited state of nuclei near the proton drip line within the Gamow-like model (GLM) and modified Gamow-like model (MGLM). The calculated results were highly consistent with the theoretical values obtained using the unified fission model [Chin. Phys. C 45 , 124105 (2021)], effective liquid drop model, and generalized liquid drop model [Acta Phys. Sin 71 , 062301 (2022)]. Furthermore, utilizing the GLM and MGLM, we predicted the 2p radioactivity half-lives from the excited state for some nuclei that are not yet available experimentally. Simultaneously, by analyzing the calculated results from these theoretical models, it was found that the half-lives are strongly dependent on Q 2p and ℓ .